Du jeune lecteur-collectionneur au concepteur de gadgets pour l’enfance : entretien avec Philippe Baumet - Lucas Profillet (Strenae)
Philippe Baumet was in charge of the conception of the gadgets for 53 issues of French weekly Pif Gadget between 2004 and 2008. This interview was an opportunity to ask him about three complementary facets of his career: that of a young and assiduous reader of Pif Gadget, that of a passionate collector and finally that of a designer of gadgets for the magazine.